2001
DOI: 10.1046/j.1365-2222.2001.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IgE and IgG binding epitopes on β‐ and κ‐casein in cow's milk allergic patients

Abstract: Information regarding the immunodominant epitopes in beta- and kappa-casein may be important for understanding the pathophysiology and natural history of CMA. Differences in epitope recognition may be useful in identifying children who will have persistent milk hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
0
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 14 publications
11
123
0
7
Order By: Relevance
“…This has also been observed in other CMA studies [24, 25]. For milk allergy, IgE binding to certain linear epitopes seem to predict persistence of allergy [26,27,28]. However, it cannot predict the time point when tolerance has developed [13].…”
Section: Discussionsupporting
confidence: 56%
“…This has also been observed in other CMA studies [24, 25]. For milk allergy, IgE binding to certain linear epitopes seem to predict persistence of allergy [26,27,28]. However, it cannot predict the time point when tolerance has developed [13].…”
Section: Discussionsupporting
confidence: 56%
“…In conclusion, this report completes the mapping of the sequential B-cell epitopes of the major CM proteins [5, 6, 7]. The next steps will include the determination of the AA crucial for IgE binding.…”
Section: Discussionmentioning
confidence: 67%
“…Previous work done by our group has identified the IgE-binding regions on α s1 -, β-, and ĸ-casein [5, 6]as well as on two major whey proteins [7]. In this study, overlapping synthetic peptides were used to identify IgE-binding regions of α s2 -casein in CMA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Caseins retain their IgE reactivity irrespective of their phosphorylation state. The IgE binding regions have been identified in caseins with six major and three minor epitopes found for s1 -casein (Chatchatee et al, 2001a), four major and six minor epitopes found for s2 -casein (Busse et al, 2001), six major and three minor epitopes for -casein and eight major epitopes for -casein (Chatchatee et al, 2001b). These epitopes are thermostable, possibly a reflection of the rheomorphic character of this protein.…”
Section: Protein Allergens Of Animal Originmentioning
confidence: 94%